2003
DOI: 10.1080/09712119.2003.9706767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Live Weight at Slaughter on Tissue Distribution in Kids

Abstract: Arguello, A., Capote, J., Marichal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The growing and feeding system are great concern to meat quality as almost all animals are raised on farms. Argüello et al [59] found that the kids grown on milk replacer had less water holding capacity and were lighter as compared to those grown by their dams. Sink and Caporaso [60] said that in flavor intensity of mutton, animal nutrition plays a key role and this flavor can be increased by the addition of legumes and grains.…”
Section: On-farm Factors Affecting Meat Qualitymentioning
confidence: 99%
“…The growing and feeding system are great concern to meat quality as almost all animals are raised on farms. Argüello et al [59] found that the kids grown on milk replacer had less water holding capacity and were lighter as compared to those grown by their dams. Sink and Caporaso [60] said that in flavor intensity of mutton, animal nutrition plays a key role and this flavor can be increased by the addition of legumes and grains.…”
Section: On-farm Factors Affecting Meat Qualitymentioning
confidence: 99%